"Enhanced Recovery" Protocol Compliance Influences Length of Stay: Resolving Barriers to Implementation. Issue 6 (June 2018) - Zoog, Evon; Simon, Remil; Stanley, J. Daniel; Moore, Richard; Lorenzo-Rivero, Shauna; Shepherd, Brian; Gao, Cuilan; Nelson, Eric
Initial implementation and maintenance of an enhanced recovery protocol (ERP) is complex and has not been adequately described. The aim of this study was to investigate the efficacy of an ERP at a tertiary care academic institution. A secondary aim was to identify barriers to implementation and continued protocol compliance (PC) to further decrease length of stay (LOS). Patients undergoing colon resection from February 2, 2011 to December 19, 2014 were compared with patients that followed implementation of an ERP from August 10, 2015 to July 14, 2016. The primary endpoint was LOS. Secondary endpoints were PC, analgesia requirements, time to return of bowel function, and ileus. One hundred and seventy-seven historical controls were compared with 68 ERP patients. LOS was shorter in study patients (4.9 vs 7.1 days for open surgery; 3.3 vs 6.1 for laparoscopic surgery). Intraoperative IVF balance, morphine equivalents, and length of time to return of bowel function were significantly less in the ERP group (1445.89 ± 845.25 mL vs 3006.08 ± 1197.97 mL), (64.48 ± 114.49 vs 232.90 ± 541.47), (2.41 ± 1.32 days vs 3.82 ± 2.00 days). Rate of ileus was less in study patients (4.8 vs 14.7%). The readmission rate and 30-day National Surgical Quality Improvement Program complication rates were not significantly different. PC was negatively associated with LOS (r = -0.35, P = 0.0026). Similar to prior studies, this study demonstrates the efficacy of an ERP. Increased PC is associated with decreased LOS, thus providing further evidence that ERPs should be the standard of care. Scheduled interdisciplinary meetings to discuss patient outcomes and methods to increase PC can help further improve efficacy of ERPs.